Implementation of management accounting tools for performance measurement in the context of New Public Management – an institutional approach - Zarzycka, Ewelina; Michalak, Marcin (Journal of Public Governance, 2014)
If private sector’s good management practices are to be used effectively to manage public sector entities, some management-aiding tools have to be introduced, particularly in the public sector’s accounting system oriented to external reporting, which needs to be supplemented with a management accounting subsystem. The main research objectives of this paper are:– to identify management accounting methods and tools currently used by the managers of the sampled local government entities – LGEs;– to evaluate the usefulness, adequacy, and eff ectiveness of performance measurement systems used in LGEs.